2008
DOI: 10.1007/bf03172750
|View full text |Cite
|
Sign up to set email alerts
|

Teacher judgments and pupils’ causal explanations: Social valorization of effort-based explanations in school context

Abstract: Achievement evaluation in school contexts may be considered as a kind of social judgment, which is affected by social and moral determinants since it is not merely an estimation of pupils' accomplishment (Dompnier, Pansu, & Bressoux, 2006;Weiner, 2003). Teachers' judgments have been investigated starting from the analysis of two theoretical approaches: the norm of internality (Dubois, 2003), and the attributional approach to social motivation (Weiner, 2006). In order to study the social valorization of interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This result confirms existing literature, which revealed that teachers with an incremental theory are likely to focus more on students' strategy and effort in learning (Lee 1996) and to establish motivational climates consistent with a mastery classroom goal structure (Bra ˚ten and Strømsø 2004;Leroy et al 2007;Trouilloud et al 2006). Moreover, our results contribute to a better understanding of the process of connecting teachers' implicit theories of intelligence to their behavior, which was not clearly demonstrated by previous research (Deemer 2004;Matteucci 2007;Matteucci et al 2008). Indeed, according to our results, teachers' beliefs about the malleability of intelligence may boost their feeling of being responsible for educational outcomes (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…This result confirms existing literature, which revealed that teachers with an incremental theory are likely to focus more on students' strategy and effort in learning (Lee 1996) and to establish motivational climates consistent with a mastery classroom goal structure (Bra ˚ten and Strømsø 2004;Leroy et al 2007;Trouilloud et al 2006). Moreover, our results contribute to a better understanding of the process of connecting teachers' implicit theories of intelligence to their behavior, which was not clearly demonstrated by previous research (Deemer 2004;Matteucci 2007;Matteucci et al 2008). Indeed, according to our results, teachers' beliefs about the malleability of intelligence may boost their feeling of being responsible for educational outcomes (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Teachers’ attributions for student performance have also been found to impact teachers’ instructional behaviors. Findings show attributions for poor student performance to low ability to correspond with encouragement of students and willingness to provide assistance, with attributions for student failure to low effort generating more criticism toward students, negative feedback, and a lower tendency to offer help (e.g., suggestions; Cooper and Lowe, 1977; Tollefson and Chen, 1988; Butler, 1994; Matteucci et al, 2008b; Woodcock and Jiang, 2013). Teachers also tended to call on other students to assist and offer expedited help (e.g., providing correct answers) to students perceived as low in ability and responded more strictly to students perceived as low in effort in requiring them to invest more time on future tasks (Butler, 1994).…”
Section: Resultsmentioning
confidence: 96%
“…One such program is Attributional Retraining (AR); an intervention typically administered to students that encourages causal attributions for failure experiences that are personally controllable in nature, while at the same time discouraging attributions that either absolve responsibility through external attributions or focus instead on internal, uncontrollable factors (e.g., low ability; for reviews, see Haynes et al, 2009). Whether addressing teachers’ attributions for student outcomes (interpersonal) or their own teaching-related setbacks (intrapersonal), attribution-informed interventions such as AR are expected to prove effective in facilitating adaptive changes in teachers’ willingness to assist students (e.g., Tollefson and Chen, 1988; Matteucci et al, 2008b; Woodcock and Jiang, 2013) as well as their own psychological and physical health (e.g., see Hall et al, 2007 for similar AR methods with students; Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a conflict between the perceptions of teachers and those of the peer group. Matteucci et al (2008) found that when teachers believed that a child's failure was a result of poor effort, their subsequent educational intervention was more severe and "with retributive purpose" (p. 29). When teachers ascribed failure to a lack of effort, they had an emotional "angry" response, but when they perceived that the pupil was not responsible for the failure their emotional response was sympathetic.…”
Section: Social Value Of Effortmentioning
confidence: 99%